2019
DOI: 10.3389/fnut.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis Between Maternal Feeding Practices and Body Mass Index (BMI): A Study in Asian Singaporean Preschoolers

Abstract: Bidirectional studies between maternal feeding practices with subsequent child weight are limited, with no studies in Asian populations. In longitudinal analyses, we assessed the directionality of the associations between maternal feeding practices and body mass index (BMI) in preschoolers. Participants were 428 mother child dyads from the GUSTO (Growing Up in Singapore Toward healthy Outcomes) cohort. Feeding practices were assessed using the Comprehensive Feeding Practices Questionnaire (CFPQ) at age 5 y. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 66 publications
(102 reference statements)
1
13
0
Order By: Relevance
“…Previous research suggests that parental feeding practices, particularly restriction, can independently contribute to and moderate the link between children’s EAH and adiposity (Birch et al, 2003, Cutting et al, 1999, Fisher and Birch, 2002), but parental behaviours can also be a consequence of the child’s weight status (Costanzo and Woody, 1985). A recent study from our GUSTO cohort also showed that the relationship between parental feeding practices and children’s weight gain between 4-6 years is bi-directional (Quah et al ., Under review). Children who show EAH in the laboratory setting may be at risk of weight gain if they have opportunities to habitually express this behaviour in their usual environment, and that will be affected by parenting style and feeding practices.…”
Section: Discussionmentioning
confidence: 65%
“…Previous research suggests that parental feeding practices, particularly restriction, can independently contribute to and moderate the link between children’s EAH and adiposity (Birch et al, 2003, Cutting et al, 1999, Fisher and Birch, 2002), but parental behaviours can also be a consequence of the child’s weight status (Costanzo and Woody, 1985). A recent study from our GUSTO cohort also showed that the relationship between parental feeding practices and children’s weight gain between 4-6 years is bi-directional (Quah et al ., Under review). Children who show EAH in the laboratory setting may be at risk of weight gain if they have opportunities to habitually express this behaviour in their usual environment, and that will be affected by parenting style and feeding practices.…”
Section: Discussionmentioning
confidence: 65%
“…More recent studies suggested that the associations between children’s BMI and parental feeding practices are bi-directional [ 30 , 32 , 35 , 50 , 51 ]. Longitudinal studies found that parental restrictive practices are developed in reaction to higher BMI in children, whereas parental pressure to eat develops in reaction to lower BMI in children [ 30 , 32 , 33 , 34 , 35 ], and the influence of children’s BMI on parental feeding practices appeared more important than the influence of parental feeding practices on children’s weight gain [ 30 , 32 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…This latter hypothesis would be consistent with our finding that mothers made more attempts to slow children's eating when they were consuming more energy, as this "slowing" behavior has not previously been shown to increase children's intake. The idea that parents adopt feeding practices in reaction to their children's eating behaviors or weight status also has some support from longitudinal studies in the literature [26,32,33,42]. Intervention studies or time-stamped behavioral observations that allow detailed analysis of the order of behaviors would be needed to confirm which behavior precedes the other and if there is a causal link.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationships between feeding practices and children's eating behaviors or weight status may differ between families of different ethnicities [21,25], overall, the general patterns found from recent studies in Asian populations reflect those seen in European or American samples. For example, studies consistently find greater pressure to eat when the child has a lower weight status, and more restriction in children with higher weight status [24,26]. A recent study of Singaporean parents has shown that parent-reported modeling healthy eating was associated with greater child intake of vegetables and whole grains, and less intake of sweet snacks and fast foods [27].…”
Section: Introductionmentioning
confidence: 99%